Electrochemical Oxidative Cross‐Coupling of Enaminones and Thiophenols to Construct C−S Bonds. Issue 23 (26th October 2020) - Lu, Fangling; Zhang, Kan; Wang, Xiaoyu; Yao, Yanxiu; Li, Liangsen; Hu, Jianguo; Lu, Lijun; Gao, Ziwei; Lei, Aiwen
Abstract: An electrochemical oxidative C(sp 2 )‐H sulfuration has been developed. Various enaminones and thiophenols were compatible, generating the desired alkenyl sulfur compounds in up to 87 % yield. This transformation proceeded smoothly under mild reaction conditions without external oxidant and transition‐metal catalyst. Remarkably, thiophenols selectively coupled with enamines when substrates had other alkenyl groups. In addition, the desired products could be further transformed into a series of α‐sulfur isoxazoles, which are a kind of useful heterocycles in materials and bioactive molecules. Abstract : Carbon−Sulfur Bond Formation . An efficient and environmentally electrosynthesis of β‐amino sulfide from enamines and thiophenols under metal‐free and external oxidant‐free conditions has been developed. A broad range of enamines and thiophenols were compatible and the reaction could be conducted in gram scale with high reaction efficiency.